POGZ promotes homology‐directed DNA repair in an HP1‐dependent manner. (10th November 2021) - Heath, John; Cheyou, Estelle Simo; Findlay, Steven; Luo, Vincent M; Carpio, Edgar Pinedo; Lee, Jeesan; Djerir, Billel; Chen, Xiaoru; Morin, Théo; Lebeau, Benjamin; Karam, Martin; Bagci, Halil; et al.
Abstract: The heterochromatin protein HP1 plays a central role in the maintenance of genome stability but little is known about how HP1 is controlled. Here, we show that the zinc finger protein POGZ promotes the presence of HP1 at DNA double‐strand breaks (DSBs) in human cells. POGZ depletion delays the resolution of DSBs and sensitizes cells to different DNA‐damaging agents, including cisplatin and talazoparib. Mechanistically, POGZ promotes homology‐directed DNA repair by retaining the BRCA1/BARD1 complex at DSBs in an HP1‐dependent manner. In vivo CRISPR inactivation of Pogz is embryonically lethal. Pogz haploinsufficiency (Pogz + /delta) results in developmental delay, impaired intellectual abilities, hyperactive behaviour and a compromised humoral immune response in mice, recapitulating the main clinical features of the White Sutton syndrome (WHSUS). Pogz + /delta mice are further radiosensitive and accumulate DSBs in diverse tissues, including the spleen and brain. Altogether, our findings identify POGZ as an important player in homology‐directed DNA repair both in vitro and in vivo . Synopsis: The zinc finger protein POGZ facilitates homologous recombination, irrespective of cell type, by retaining the HP1‐gamma‐BARD1‐BRCA1 complex at DSB. POGZ is required for template‐dependent DNA repair (HR/SSA). POGZ deficiency reduces the recruitment of HP1‐gamma and the BRCA1/BARD1 complex to sites of DNA damage. Heterozygous loss of POGZ results in growth defects, abnormal behavior and aberrant DSBs in multiple tissues. Pogz + /delta B cells show reduced class switch recombination. Abstract : The zinc finger protein POGZ facilitates homologous recombination, irrespective of cell type, by retaining the HP1‐gamma‐BARD1‐BRCA1 complex at DSB.